PROMOTION AND PRODUCT QUALITY ON CUSTOMER LOYALTY: THE ROLE OF MEDIATION IN CUSTOMER SATISFACTION OF ERIGO PRODUCTS - Donny Arif; Riska Yulianti; Rezki Aulia Pramudita (Universitas Maarif Hasyim Latif, 2023)
The purpose of this study: is to examine the effect of promotion and product quality on customer loyalty: the mediating role of Erigo product customer satisfaction. This study uses descriptive quantitative research with a sampling technique, namely a random sampling technique with a sample of 100 respondents. Data was obtained by distributing questionnaires in the Sidoarjo area, Taman sub-district. The analysis technique used is path analysis with the help of the SmartPLS program. Based on the data analysis conducted in this study shows that promotions positively and significantly affect customer loyalty in purchasing Erigo products. Advertising ultimately and significantly affects customer satisfaction in purchasing Erigo products. Product quality substantially affects customer loyalty in purchasing Erigo products. Product quality positively and significantly affects customer satisfaction in product purchases. Customer satisfaction wholly and substantially affects customer loyalty in purchasing Erigo products.